Plant Vegetation of Waru-Waru Forest Region, Sempu Island Nature Reserve - Esti Endah Ariyanti; Deden Mudiana (Media Konservasi, 2018)
Waru-waru Forest Region is a designation for one of the areas to the northern part of the Sempu Island Nature Reserve (CAPS), which is an easy area to get to by boat because of its sloping beaches. The name of this region refers to many waru trees (Hibiscus tiliaceaus) that found growing around the beach area. In general, the CAPS forest condition is still quite good, including in the Waru-waru Forest Region. Only a few meters from the shoreline, natural vegetation conditions can be found. This study aims to determine the composition of plant vegetation in the Waru-waru Forest Region (CAPS). As many as 33 species of trees were recorded in this study, with individual tree density of 162.5 trees / ha. The results of vegetation analysis carried out showed that the tree vegetation in the region was dominated by species: Pterospermum javanicum, Syzygium syzygioides, and Excoecaria agallocha. At the pole level the dominant species are Drypetes longifolia, Canarium sp. and Pterospermum diversifolium. Orophea hexandra, Drypetes longifolia, Cyathocalyx sumatranus, Mallotus moritzianus, Pterospermum javanicum, and Buchanania sp. are species of tree regeneration that dominate at the sapling level. Tree seedlings are dominated by Mallotus moritzianus and Pterospermum javanicum. Keywords: Sempu Island Nature Reserve, Waru-Waru Forest Region, vegetation